Developing edible oleogels structure prepared with emulsion-template approach based on soluble biopolymer complex - Mozhdeh Sarraf; Sara Naji-Tabasi; Adel Beig-Babaei; José Enrique Moros; Maria Carmen Sánchez Carrillo; Adrián Tenorio-Alfonso (Food Chemistry: X)
The utilization of edible oleogels as oil structures has been proven to comprise a suitable alternative to fat. In this research, whey protein concentrate (WPC) oleogel structure was designed and improved by the creation of a soluble complex of WPC-basil seed gum (BSG) and WPC-xanthan gum (XG) at different concentrations (0.2, 0.4, and 0.6 % w/w). The results showed increasing the hydrocolloids had positive effects on oleogel characteristics, which can preserve oil well in the microstructure network of oleogel. Additionally, the incorporation of hydrocolloids promoted stability of oleogels against stress and heat. Therefore, the centrifuge stability of WPC oleogel was 26 and increase to ∼98 and 100 % in 0.6XG:WPC and 0.6BSG:WPC oleogels, respectively. The evaluation of the rheological properties revealed the predominant elastic behavior of the oleogles. Overall, the addition of either XG or BSG into WPC-based oleogel improved its physicochemical and mechanical characteristics. Moreover, oleogels prepared using 0.6 % BSG-5 % WPC exhibited the best properties.